Pengungkapan Tanggung Jawab Sosial dalam Perspektif Syariah Enterprise Theory - Ratna Kusuma Dewi; Rifqi Muhammad (Faculty of Economics, Universitas Internasional Batam, 2022)
Purpose - The purpose of this study is to provide knowledge and information about the level of disclosure of social responsibility in Islamic banks in the perspective of sharia enterprise theory (SET) in 2017. Research Method - This study is a quantitative study using data on social responsibility reports for the period of 2017 with a sample of 3 Islamic banks in Indonesia, namely BSM, BTN Syariah, and BPRS Bhakti Sumekar. The analytical method used is the content analysis method (Content Analysis). Findings - The findings show that BSM has the highest level of social responsibility disclosure with a score of 31 points (74%) followed by BTN Syariah with a score of 26 points (62%), while BPRS Bakti Sumekar gets a score of 19 points (45%). Implication - The implications of this research can provide input for regulations to further encourage banks to carry out CSR activities as a form of awareness and corporate social responsibility to the community.